Pendekatan Teknik Client Centered Untuk Meningkatkan Pemahaman Identitas Diri Pada Waria - Nadia Permatawati; Suryati Suryati; Neni Noviza (Social Science and Contemporary Issues Journal, 2023)
This research is titled "Client Centered Technique Approach in improving the Understanding of Self Identity in Waria". Self-identity is basically something that is considered very important by every individual, because self-identity is a principle of unity that distinguishes oneself from other people. Physically, transvestites are one of the persons with social welfare problems who experience deviations in the formation of imperfect personalities and are commonly found in Indonesia. The purpose of this study is to determine the description of understanding of self-identity, the factors that cause low self-identity and the application of client centered techniques to improve understanding of transgender self-identity. Therefore, this research uses a type of field research, qualitative approach and descriptive qualitative method. The subjects of this research are transgender people assisted at the PKBI South Sumatra Institute, namely client "LF", client "M" and client "AS". Techniques used in collecting research data include observation, interviews and documentation. The results of the study after completing the counseling stages with 5 meetings and 3 steps of the client centered technique approach on client "LF", client "M" and client "AS" it is known that before the client centered technique is carried out, perceive various aspects of themselves as a harmony and desire not in accordance with their identity. However, after the client centered technique, their understanding of self-identity has undergone a development where they have been able to understand well the self-identity they have. The causative factors that most influence the low self-identity of clients are parents, peer groups, social interactions and work experience. Keywords: Client centered, Self-identity, Waria.